VD_FINDINFO HC / 2016 / 682 vom 27. Juni 2016 - VD Tribunal cantonal (2016)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, DROIT DE GARDE, MAJORITÉ{ÂGE} | 163 CC, 176 CC, 278 al. 2 CC, 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH), 314 al. 1 CPC (CH), 314 al. 2 CPC (CH)